The Role of Specialized Pro-Resolving Mediators in Cystic Fibrosis Airways Disease - Briottet, Maelle; Shum, Mickael; Urbach, Valerie (Frontiers in Pharmacology, 2020)
Cystic Fibrosis (CF) is a recessive genetic disease due to mutations of the Cystic Fibrosis Transmembrane conductance Regulator (CFTR) gene encoding the CFTR chloride channel. The ion transport abnormalities related to CFTR mutation generate a dehydrated airway surface liquid (ASL) layer, which is responsible for an altered mucociliary clearance, favors infections and persistent inflammation that lead to progressive lung destruction and respiratory failure. The inflammatory response is normally followed by an active resolution phase to return to tissue homeostasis, which involves specialized pro-resolving mediators (SPMs). SPMs promote resolution of inflammation, clearance of microbes, tissue regeneration and reduce pain, but do not evoke unwanted immunosuppression. The airways of CF patients showed a decreased production of SPMs even in the absence of pathogens. SPMs levels in the airway correlated with CF patients’ lung function. The prognosis for CF has greatly improved but there remains a critical need for more effective treatments that prevent excessive inflammation, lung damage and declining pulmonary function for all CF patients. This review aims to highlight the recent understanding of CF airway inflammation and the possible impact of SPMs on functions that are altered in CF airways.